Techniques and timings for cleft palate surgery: a randomised controlled trial - Vincent Kok Leng Yeow; Selena Ee-Li Young; Philip Kuo-Ting Chen; Seng Teik Lee; David Machin; Qingshu Lu (Australasian Journal of Plastic Surgery)
**Background**: There is a lack of reliable information on outcomes following cleft surgery. Options for timing and choice of primary cleft surgery have not been compared in randomised trials. **Methods**: Non-syndromic infants, aged six months, with isolated cleft of the secondary palate without associated lip deformity, were included in this prospective randomised trial to one of four options: Veau-Wardill-Kilner palatoplasty at six months of age (VWK06) or 12 months of age (VWK12), or two-flap palatoplasty with intra-velar veloplasty at six months of age (2F-IVV06) or 12 months of age (2F-IVV12). Outcome measures are early and late postoperative complications, velopharyngeal inadequacy symptoms, nasality, articulation and presence of otitis media at three years of age. **Results**: Of the 76 infants included in the trial, 90.8 per cent received surgery: VWK06 (n = 18), VWK12 (n = 16), 2F-IVV06 (n = 18) and 2F-IVV12 (n = 17). Early postoperative complications occurred in two VWK infants (6.1%) and three 2F-IVV infants (8.8%)—a difference of -2.8 per cent. With surgery planned at six months of age (T06) and 12 months of age (T12) respectively, there were three VWK infants (8.6%) and two 2F-IVV infants (6.3%)—a difference of +2.3 per cent. At age three, speech assessments were conducted for 62 (84%) children. Velopharyngeal inadequacy symptoms were detected in 4/30 VWK children (13.3%) and 3/30 2F-IVV children (10.0%)—a difference of 3.3. With T06 and T12, there were three VWK infants (9.4%) and four 2F-IVV infants (14.3%)—a difference -4.9%. Otitis media was documented in 40/61 of children (65.6%), hyper- and/or hyponasality in 27/61 of children (44%) and articulation errors in 53/60 of children (88%). **Conclusion**: Post-surgical complication rates appear low, and differ little, between VWK and 2F-IVV. At three years, there were no demonstrable differences in velopharyngeal inadequacy symptoms, nasality, articulation and otitis media between the two surgical techniques at two different times.